How Aseismic Ridges Modify the Dynamics of Free Subduction: A 3-D Numerical Investigation - Suchoy, Lior; Goes, Saskia; Chen, Fangqin; Davies, D. Rhodri (Frontiers in Earth Science, 2022)
The subduction of positively buoyant features has been implicated in the development of flat and shallow dipping slabs, the formation of cusps in trench geometry, and the cessation of associated arc magmatism. However, how such buoyant anomalies influence subduction dynamics to produce these different tectonic expressions remains debated. In this paper, using a series of multi-material 3-D simulations of free subduction, we investigate how linear buoyant ridges modify subduction dynamics, in particular downgoing plate velocities, trench motions and slab morphology. We examine the sensitivity of results to downgoing plate age (affecting buoyancy and strength), ridge buoyancy and ridge location along the trench, finding that buoyant ridges can locally change slab sinking and trench retreat rates, in turn modifying the evolution of slab morphology at depth and trench shape at the surface. In all cases examined, trench retreat is reduced, or switches to trench advance, where the ridge subducts. These effects depend strongly on downgoing plate age: on young, weak plates, the change in trench shape is more localised than on old, strong plates. Slab shallowing at the ridge only occurs for young plates, while the stronger and more negatively buoyant older plates pull down the ridge at a steeper angle than the rest of the slab. On old plates, ridges located near regions of trench stagnation or advance, which typically develop in wide slabs, have a stronger effect on trench and slab shape. The combined effects of buoyant feature location, subducting plate age and overriding plate properties can result in a range of responses: from mainly trench deformation, through local slab shallowing, to the formation of a flat slab, a variation in expressions also observed on Earth.